Pemberdayaan masyarakat dalam kegiatan penyemprotan disinfektan sebagai upaya pencegahan Covid-19 - Yustika, Ana; Wijayanti, Aprin Wahyu; Ummah, Ana Khoirul; Dhaningtyas, Shalihat Afifah (Nur Science Institute, 2022)
One of the efforts to prevent the spread of the Covid-19 virus is to spray disinfectants around their living environment. In this service activity, the service team divided the activities into several stages, namely (1) socialization of activities; (2) implementation of activities; and (3) activity evaluation. Socialization of activities carried out to provide information to the public about activities. The implementation of the activity begins with assistance in making disinfectants and continues with spraying disinfectants into public areas and residents' homes. The service activity was closed with an activity evaluation meeting which concluded that the spraying of disinfectants as an effort to prevent covid-19 could run well through a community empowerment program in Kupang Village, Ambarawa District.